A Noval Approach on Triangular Fuzzy Unisum Labeling in Pharmaceutical Research (Journal of Pharmaceutical Negative Results, 2022)
Triangular fuzzy graph labeling is used to create a networking model in the field of pharmaceutical research which will provide a structure for taking advantage of proposed medicines and segregate suitable compounds in case of vagueness of dataset of medicines. Especially all acyclic fuzzy graphs are most commonly used to represent a pharmaceutical model. In this paper,Triangular fuzzy unisum labeling has been introduced which is used to attain the accuracy value in the consecutive distinct edge labeling. Also the researcher have been shown the existence of unisum labeling in triangular fuzzy bistar graph 〖 B〗_(m,n):(σ,μ) ∀ m,n . Also the researcher have been proved the results such that every triangular fuzzy bistar graph admits the condition of unisum labeling which is leading to obtain the triangular fuzzy graceful bistar graph.